Efektivitas Program Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) Di Kecamatan Denpasar Barat - Heryendi, Wycliffe Timotius (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 2, Agustus 2013 (pp. 71-143), 2013)
BKKBN develop a family welfare income increasing program (UPPKS) associated with the implementation of Family Planning (KB) aims to improve the well-being of families through economic enterprise. The study was conducted on members UPPKS Program beneficiaries in the District of West Denpasar. This study aims to determine the effectiveness of the program, and the benefits of highly rated programs of welfare after receiving assistance UPPKS Program. This study uses a quantitative approach with a survey method that collected information from respondents through questionnaires and in-depth interviews (in-depth interview). The sampling method used is proportionate stratified random sampling with a sample size of 90 respondents. Analysis techniques used are descriptive statistics and Mc Nemar test. The results of this study indicate that the implementation is very effective UPPKS Program, which is 86.56 percent of the respondents stated that the program is implemented in accordance with the expectations and goals of the program and Mc Nemar tests indicate a change in the level of welfare of the respondents significantly increased revenue and employment seen from working hours of respondents at the time before and after the program Sub UPPKS in West Denpasar.
Keywords: UPPKS programs; effectiveness; well-being